Numerical study on shell and tube heat exchangers with different baffles configurations - Yousef, Ahmed; Saim, Rachid; Öztop, Hakan Fehmi F. (Emerald Group Publishing Ltd, 2023)
PurposeThe purpose of this paper is to give a comparison between different type of baffles for a better application. Computational analysis of heat transfer and fluid flow through plain, flower and perforated baffles for heat exchanger. Design/methodology/approachNumerical simulations for heat exchangers with plain, flower and perforated baffles are carried out with finite volume method. The thermal-hydraulic performance for the three types is presented in the same conditions. FindingsThe perforated baffles generate low shell pressure with high Nusselt number; transverse baffles give the best heat transfer with high pumping power. The overall performance coefficient of these three types of heat exchangers shows that the perforated baffles have a highest and the transverse baffles have the lowest. Analysis of the results show that perforated transverse baffles produce pressure drop lower by 6.68% than transverse baffles and 2.64% lower than flower baffles. The pumping power for perforated transverse baffles lower by 13.3% to the transverse baffles and 4.72% lower than that of flower baffles. The Nusselt number for perforated baffles higher by 4.16% to the flower baffles and 2.77% with transverse baffles. The overall performance factor in the heat exchanger with perforated baffles higher by 5.55% to that with transverse baffles and 3.46% with flower baffles. Recirculation areas are reduced in shell with perforated baffles and velocity distribution becomes more uniform. Originality/valueUsing of perforated baffles in heat exchanger give the best overall performance factor.
Keywords: Numerical; Heat transfer; Heat exchanger; Baffles